Cross-Border Merger and Acquisition In Asean: A Comparative Study To The Merger Control Regulations of The European Union - Catur Septiana Rakhmawati; Irna Nurhayati (Journal of Private and Commercial Law, 2024)
This research aims to analyze (1) the weaknesses of ASEAN Regional Guidelines on Competition Policy on Merger Control Regulation compared to similar regulations in the European Union; and 2) the improvement of the ASEAN regional guidelines that needs to be undertaken related to Merger Control Regulation based on the lessons learned through the studies of regulations in the European Union. This is a normative legal study that was conducted through library research by tracing secondary data in the form of primary, secondary, and tertiary legal materials. The data were analyzed using qualitative analysis. This study found that the weaknesses of ASEAN Regional Guidelines as follow: first, the nature of ASEAN Regional Guidelines that uses soft-law approach leads to the diversity of regulations among ASEAN member states; second, no institution in the ASEAN level has the authority to enforce the said competition law, particularly in regards to cross-border M&A. The substantive test under ASEAN Regional Guidelines uses the Significant Impediment to Effective Competition (SIEC) model. It does not contain any detailed provisions and has lack of indicators. Notification under the ASEAN Regional Guidelines recognizes both mandatory and voluntary notification, yet it does not specify which notification that should be implemented. Furthermore, lessons learned from the study of the regulations in the European are the use of both soft-law and hard-law approaches; the establishment of an institution in the ASEAN level; the clarity of indicator or parameter regarding the substantive test or assessment; and the notification shall be implemented as well as its mechanism. Keywords: Merger Control, ASEAN Regional Guideline, European Union Abstrak Penelitian ini bertujuan untuk menganalisis (1) kelemahan ASEAN Regional Guidelines on Competition Policy dibandingkan dengan peraturan serupa di Uni Eropa; dan (2) bagaimana seharusnya ASEAN Regional Guidelines on Competition Policy pada masa yang akan datang berdasarkan lesson learned yang diperoleh melalui kajian pengaturan di Uni Eropa. Penelitian ini merupakan penelitian hukum normatif yang dilakukan melalui studi pustaka dengan menelusuri data sekunder berupa bahan hukum primer, sekunder, dan tersier. Data dianalisis dengan menggunakan analisis kualitatif. Penelitian ini menemukan bahwa kelemahan ASEAN Regional Guidelines adalah; pertama, sifat dari ASEAN Regional Guidelines yang menggunakan pendekatan soft-law menyebabkan adanya keragaman peraturan di antara negara-negara anggota ASEAN; kedua, tidak ada lembaga di tingkat ASEAN yang memiliki kewenangan untuk menegakkan hukum persaingan usaha tersebut, khususnya terkait M&A lintas negara (cross border). Uji substantif di bawah ASEAN Regional Guidelines menggunakan model Significant Impediment to Effective Competition (SIEC). Model ini tidak memuat ketentuan-ketentuan yang rinci dan memiliki indikator yang kurang. Notifikasi di bawah ASEAN Regional Guidelines mengakui adanya notifikasi wajib dan sukarela, namun tidak menentukan notifikasi mana yang harus dilaksanakan. Selain itu, lesson learned yang dapat diambil dari studi pengaturan di Uni Eropa adalah penggunaan pendekatan soft-law dan hard-law; pembentukan lembaga di tingkat ASEAN; kejelasan indikator atau parameter terkait uji substantif atau penilaian; dan notifikasi yang harus dilakukan serta mekanismenya. Kata Kunci: Kontrol Merger, ASEAN Regional Guideline, Uni Eropa